Surgical applied anatomy: alive and kicking. Issue 5 (18th March 2021) - Farley, Edward; Hindmarch, Jake; Eizenberg, Norman; Midwinter, Mark
Abstract: Background: Contention exists amongst anatomists, clinicians and surgeons about how much anatomical knowledge medical students need, although what is taught should be aligned with current surgical practice. The aim of this study was to explore the scope of recent advances in applied anatomy as highlighted in the ANZ Journal of Surgery in each of the surgical specialties. Methods: The 2018 volume of the ANZ Journal of Surgery was narrowed to 254 articles by applying the search term 'anatomy'. The main topic was extracted from each paper. The content of the paper was assessed for 'novel description' or 'novel application' of anatomical knowledge and classified accordingly. Results: Most papers with an anatomical focus were from general surgery, which focused on surgical techniques, outcomes and management. Vascular surgery had the highest percentage of papers with a novel description and application of anatomy. Although cardiothoracic and paediatric surgery had no papers with a novel description of anatomy, novel applications of anatomy were a focus in each speciality. Conclusion: The trend towards novel applications of anatomical knowledge in all surgical specialties should encourage medical schools to shape their anatomy curricula in tandem with such advances as they evolve. The high proportion of novel applications and descriptions of anatomy in general surgery indicates continued growth as a benchmark of anatomical understanding. Vascular surgery's proportion of novel application and description of anatomy may change the way students will learn vascular anatomy to incorporate endovascular, radiologically based approaches. Abstract : The application of anatomical knowledge remains central to the discipline of surgery as well as many other clinical specialties. Applied anatomy has undergone a renaissance with new modalities to treat diseases, particularly with minimally invasive access and novel anatomical approaches. It is therefore timely, we believe, to review how anatomy is being applied in the contemporary literature in order to inform how to both support students in their understanding of anatomical principles of these novel approaches, and also to foster future innovation. These new approaches have also led to some pathologies previously considered 'surgical', which are being treated by other non‐surgical approaches or a multidisciplinary approach. Thus, such changes are of wider interest. By demonstrating that applied anatomy is both relevant and developing (alive and kicking), the necessity of maintaining its central place in the medical curriculum is clear, but a review of the detail of the anatomy curriculum is worthy of further examination.